PENERAPAN SISTEM PERIZINAN BERUSAHA ONLINE SINGLE SUBMISSION RISK-BASED APPROACH (OSS-RBA) DI BIDANG INDUSTRI PASCA UU CIPTA KERJA - Ida Ayu Kade Febriyana Dharmayanti; Putu Gede Arya Sumerta Yasa (Jurnal Komunikasi Hukum, 2022)
The objective of this study is to establish the business licensing arrangements in Indonesia after the enactment of the Undang-Undang Cipta Kerja and to find out the problems of implementing the business licensing system in the industrial sector through the Online Single Submission Risk-Based Approach (OSS-RBA) after the enactment of the Job Creation Act. The research method used in this research is empirical legal research, with a statute approach, analitical and conseptual approach, and facts approach. This research is descriptive by using qualitative analysis. The results of this study is business license or industrial license management system in Indonesia has experienced various dynamics which aim to continue to improve and become better in the future. This dynamic encourages various kinds of changes regarding business license and industrial license, starting from the laws and regulations to its practice. The use of online-based OSS-RBA when the verification process often experiences problems, so that in the future the government or authorized agencies are expected to be able to refine the OSS-RBA system therefore that problems would not be happened in its practice.